Pendampingan Branding Dan Digital Marketing Untuk Meningkatkan Penjualan Produk UMKM Catering Di Kelurahan Kepanjen Kidul, Kota Blitar - Junita Pramita Sari; Nurjanti Takarini (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Based on the problems faced by UMKM Catering in the Kepanjen Kidul sub-district, Blitar City, it is necessary to have training in digital marketing strategies and product brand recognition so that they are known in a wider market. The method used in this service is to provide solutions to MSME catering problems, including branding assistance and digital marketing strategies through social media. Based on the results of the service that has been carried out including making logos, brochures, catalogs, banners and creating social media accounts as online marketing media, the dedication program in branding and digital marketing assistance to UMKM Catering has gone well because UMKM Catering owners can gain new knowledge and skills to be applied to its business with the aim of increasing product competitiveness and increasing product sales revenue.